Association Between Toothbrushing Frequency and Oral Hygiene Status Among University Students - Febi Magfirah; St.Nur Eni; Astri Annur Qalbi (Jurnal Ilmu Kesehatan Nusantara, 2024)
Background: Oral hygiene is an essential component of overall health, and regular toothbrushing is the primary preventive measure for maintaining oral cleanliness and preventing dental diseases. However, inadequate toothbrushing practices remain common among university students, potentially resulting in poor oral hygiene. Understanding the relationship between toothbrushing frequency and oral hygiene status is important for developing effective oral health promotion programs among future healthcare professionals. Research Objective: This study aimed to determine the association between toothbrushing frequency and oral hygiene status among students of STIKES Amanah Makassar. Methods: This analytical observational study employed a cross-sectional design involving 42 students selected through purposive sampling. Toothbrushing frequency was assessed using a structured questionnaire and categorized as less than twice daily or at least twice daily. Oral hygiene status was evaluated through clinical examination using the Oral Hygiene Index-Simplified (OHI-S). Descriptive statistics were used to summarize respondent characteristics, while the Chi-square test was applied to examine the association between toothbrushing frequency and oral hygiene status with a significance level of p < 0.05. Results: Most respondents brushed their teeth at least twice daily (66.7%) and had a fair oral hygiene status (47.6%). Students who brushed their teeth at least twice daily showed a higher proportion of good oral hygiene (46.4%) than those who brushed less frequently. The Chi-square test revealed a statistically significant association between toothbrushing frequency and oral hygiene status (p = 0.008). Conclusion: Toothbrushing frequency was significantly associated with oral hygiene status among students of STIKES Amanah Makassar. Promoting regular toothbrushing accompanied by proper brushing techniques and routine oral health education may improve oral hygiene and reduce the risk of oral diseases among university students.